Breakup dynamics of emulsion droplet and effects of inner interface. (October 2022) - Pang, Yan; Lu, Yao; Zhou, Qiang; Wang, Xiang; Wang, Ju; Li, Mengqi; Liu, Zhaomiao
Abstract: The size and the dispersibility of droplets are the significant factors that determine the performance in applications of the emulsion droplets, which are controlled by the breakup characteristics of interfaces. In this paper, a four-phase glass capillary device is used to generate three-layer wrapped (O1 /O2 /W/O3 ) emulsion droplets stably, recording the evolution of interfaces to investigate the breakup characteristics of interfaces under different flow rates. Based on the breakup form of interfaces, the phase diagram which is recorded by the flow rate ratios ( α, β ) shows the distribution of different generation modes, including Jetting Tubing (JT), Dripping Tubing (DT), Dripping (D), Narrow Jetting (NJ) and Widen Jetting (WJ). The interfaces are recorded with time in different generation modes in this study, focusing on the generation details of DJ, D, and NJ mode, where the droplet generates with the stable periodic motion. The inner droplets do not influence the generation modes but provide the interactions of the interfaces in some cases, especially on the neck diameter of the outer interface. In DT mode, a larger flow rate ratio intensifies the fluctuation of the interface, while it pulls the neck of the inner interface and the outer one to the similar position along the flow direction. In NJ mode, the relation between prediction length and the experimental one follows a similar scaling law to single droplets with various coefficients. Highlights: Generation modes of four-phase emulsion droplets can be separated in the phase diagram by the flow rate ratios ( α, β ). The inner phases have no effect on the distribution of formation modes, while the critical boundaries varies in each mode. Inner droplets have influences on the characteristic parameters of each mode, including the neck diameter.